'Double layer' frozen elephant trunk with balloon endoclamping: a technique to simplify the 2-stage open repair of thoraco-abdominal aortic aneurysms. (12th March 2020) - Di Eusanio, Marco; Berretta, Paolo; Cefarelli, Mariano; Gatta, Emanuele
Abstract: Staged replacement of the aortic arch and thoraco-abdominal aorta (TAA) with a frozen elephant trunk followed by TAA repair is a valuable treatment for patients with chronic TAA dissection. However, in patients with an unclampable descending thoracic aorta, the retrieval of the trunk can be problematic and the proximal stent graft-to-graft anastomosis technically challenging. Here we present our 'double layer' frozen elephant trunk technique to treat patients with TAA dissection.